FSEK Eser Sahibinin Manevi Haklarına Saldırı Halinde Talep Edilebilecek Manevi Tazminat - (:unkn) unknown (My University, 2013)
Eser sahibi manevi hakların ihlal edildiğine binaen FSEK m. 70/1 hükmüne dayanarak manevi tazminat davası açabilecektir. Öğretide ve Yargıtay kararlarında, söz konusu hükmün klasik haksız fiil rejiminin dışında bir sorumluluk öngördüğü çağrışımı yaptığı ileri sürülse de, kanaatimizce bu hüküm, klasik haksız fiil rejiminin özel bir yansımasıdır ve ihlal eylemini gerçekleştiren şahsın kusuru aranmalı, çokça dile getirildiği gibi ancak kusursuz sorumluluk hallerinde şahıs objektif sorumluluk altına sokulup manevi tazminata mahkûm edilebilmelidir.

Author can sue a case on damages for mental anguish based upon the infringement of his moral rights according to Turkish Copyright Law article 70/1. In the doctrine and Supreme Court decisions, although it is claimed that it would anticipate a liability out of the provision of the classical tort regime, according to our opinion, this provision is a special reflection of classical tort regime and it should be sought as the fault of the person who carries out the infringement act. Moreover as commonly expressed only in the case of absolute liability conditions a person should be put an obligation of an objective liability and be sentenced to the damages for mental anguish.
Damages for Mental Anguish which can Be Claimed in Turkish Copyright Law in the Case of the Offence to the Author's Moral Rights
Keywords: Hukuk